It's not about the broccoli : three habits to teach your kids for a lifetime of healthy eating - Rose, Dina (New York, New York : Perigee/Penguin Group, 2014)
"You already know how to give your kids healthy food. But the hard part is getting them to eat it. After years of research and working with parents, Dina Rose discovered a powerful truth: When parents focus solely on nutrition, their kids--surprisingly--eat poorly. But when families shift their emphasis to behaviors--the skills and habits kids are taught--they learn to eat right. Every child can learn to eat well--but only if you show them how to do it. Dr. Rose describes the three habits--proportion, variety, and moderation--all kids need to learn, and gives you clever, practical ways to teach these food skills. All children can learn: - How to confidently explore strange, new foods - How to know when they're hungry and when they're full - What to do when they say they're 'starving' --and about to attend a birthday party - How to branch out from easy-to-like prepackaged kid fare to more mature tastes and textures: savory, tangy, runny, crunchy - How to engage in open and honest talk about food without yelling, "I don't like it!" With It's Not About the Broccoli, you can teach your children how to eat, and give them the skills they need for a lifetime of health and vitality"--
"A Perigee book."
Includes bibliographical references (pages [245]-254).
Keywords: Children -- Nutrition; Natural foods; Health promotion